Tracking Research Practices within the Elementary Education Division (DEB) at Universidad Nacional: Rupture, Innovation, and Change of Paradigms - Dobles-Trejos, Cecilia (2015)
This paper established the different paradigms and trends in research practices that take place within the División de Educación Básica (Elementary Education Division-DEB, for its name in Spanish) of Centro de Investigacion y Docencia en Educación (CIDE, from its name in Spanish) at Universidad Nacional (UNA) in Costa Rica. As such, these research practices have established diverse trends towards conceiving and doing research within DEB. As a process, these practices have been created and developed throughout time while establishing a historical constant in the academic curricular dynamics of DEB -as it can be observed in the study career programs, course syllabus and final graduation projects as well. In the 1990s, research at DEB was mainly descriptive-exploratory and it was characterized by data analysis focused on descriptive statistics and linearity from a positivist approach. At the same time, educational practices linked to a social approach in communities at risk were developed, and a quality-oriented research line emerged. Currently, research work at DEB is developed from a qualitative paradigm approach, thus allowing research circularity and recursiveness. It is then concluded, that this research trend allows new possibilities regarding current socio-pedagogical demands as well as developing teaching abilities to respond to socio educational problems and social transformation.